Posts and pasts a theory of postcolonialism - López, Alfred J. 1962- (SUNY series, explorations in postcolonial studies., 2001)
"In Posts and Pasts: A Theory of Postcolonialism, Alfred J. Lopez argues for a formulation of postcolonial studies which diverges in three significant ways from current academic and institutional practices: 1) the postcolonial as diasporic, constituted by a series of dispersed and irregular criticisms not at all containable within a single set of parameters, whether historical, geographical, or socioeconomic; 2) the postcolonial as a distinct ontological moment in the life of a nation or people, in which it conceives itself as doubly haunted - on the one hand by the "memory in advance" of a collective national future and on the other by its colonial past; and 3) the postcolonial as a distinct phenomenological moment, a radical break in the history of a relation between lords and bonds-women and -men."